Tensides from a group of propylene oxide and ethylene oxide copolymers. VII. Test of utilizing critical concentrations of micella (CMC), at levels of equal density hydro-lipophilic (HLB) and measures of macroparticles (Ro, omega) in bile "A" of healthy persons and patients - Zgoda, M M; Karczewski, T (Acta Poloniae pharmaceutica, 1990)
Using the model systems of reference (nonionic surfactants of Pluronic and Rokopol type) bile "A" in healthy and ill subjects (cholelithiasis, states after cholecystectomy, catarrh, chronic duodenitis) was characterized using chosen viscosity parameters. The model experiments enable selective, preclinical estimation of solubilisation capacity of nonionic surfactants of Pluronic type and their Polish analogues Rokopols.